Development of a wearable gait detection system for racehorses - Low, J.-H.; Mak, V. W.-L.; Forbes, B.; Sepulveda, F.; Yeow, C. H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Biomechanical analysis of racehorses is important in quantifying and maintaining performance. Early detection of lameness is crucial to ensure the wellbeing and proper rehabilitation of horses, and to prevent exacerbation of the condition. The purpose of this study was to develop a limb-mounted portable wireless sensor system to investigate equine biomechanics and detect the presence of lameness in racehorses based on the lower limb kinematics. The preliminary results showed that the system can detect trotting gait cycles accurately and the lame racehorse showed a reduction in hoof flexion and extension as compared to normal racehorse.